Alpha hemolysin induces an increase of erythrocytes calcium: a FLIM 2-photon phasor analysis approach - Sánchez, Susana (2011)
α-Hemolysin (HlyA) from Escherichia coli is considered as the prototype of a family of toxins called RTX (repeat in toxin), a group of proteins that share genetic and structural features. HlyA is an important virulence factor in E. coli extraintestinal infections, such as meningitis, septicemia and urinary infections. High concentrations of the toxin cause the lysis of several cells such as erythrocytes, granulocytes, monocytes, endothelial and renal epithelial cells of different species. At low concentrations it induces the production of cytokines and apoptosis. Since many of the subcytolytic effects in other cells have been reported to be triggered by the increase of intracellular calcium, we followed the calcium concentration inside the erythrocytes while incubating with sublytic concentrations of HlyA. Calcium concentration was monitored using the calcium indicator Green 1, 2-photon excitation, and fluorescence lifetime imaging microscopy (FLIM). Data were analyzed using the phasor representation. In this report, we present evidence that, at sublytic concentrations, HlyA induces an increase of calcium concentration in rabbit erythrocytes in the first 10 s. Results are discussed in relation to the difficulties of measuring calcium concentrations in erythrocytes where hemoglobin is present, the contribution of the background and the heterogeneity of the response observed in individual cells. © 2011 Sanchez et al.